EVALUATION OF WOUND HEALING ACTIVITY OF ACACIA AURICULIFORMIS A. CUNN. STEM BARK - Singh, Sumitra; Sharma, Nidhi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate in vivo wound healing activity of ointment containing ethanol and aqueous bark extracts of Acacia auriculiformis A. Cunn. (Family: Mimosaceae). Methods: The presence of phytochemicals like carbohydrates, phenols, flavonoids, tannins and saponins was determined by preliminary phytochemical screening. Wound healing effect of ointment containing 5% w/w ethanol and aqueous stem bark extracts was determined by using excision and incision wound models in Swiss albino mice. Hydroxyproline content determination and histopathological studies of treated groups were carried out. Results: The results showed that both formulations possess significant wound healing activity, which was evidenced by decreased period of epithelialization, increased rate of wound contraction, tensile strength, hydroxyproline content, granulation tissue and collagen fibre formation in all treated animals. The activity may be due to presence of phenols, tannins, and flavonoids. Conclusion: The ointment containing ethanol extract showed better wound healing activity than the ointment containing aqueous extract. Keywords: Acacia auriculiformis, excision wound model, hydroxyproline, incision wound model, tensile strength, wound contraction